Dvārakānātha Ṭhākura, aitihāsika samīkshā - Cakrabartī, Rañjita (Granthabitāna, 1983)
On the life and works of Dwarkanath Tagore, 1794-1846, Bengali socioreligious reformer and philanthropist; historical assessment.